2022
DOI: 10.17707/agricultforest.68.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Soil Organic Carbon by Acacia Mangium Afforestation in Southeastern Region, Vietnam

Abstract: The knowledge about dynamics of soil organic carbon (SOC) accumulation and its controls are critical in understanding of the C cycling in forest ecosystems. Acacia mangium Willd. is one of the most important fast-growing afforestation tree species in Vietnam, providing significant ecological, economic, environmental, and social benefits. The existing studies offered information limited on the distribution and regulation of SOC in the A. mangium plantations. The primary purpose of this study was to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
3
2
0
Order By: Relevance
“…These results agree with those from earlier studies (Zhao et al 2014;Liu et al 2016;Cuong et al 2023). These findings may be explained by a significantly greater plant litterfall production and fine-root turnover in older plantations and a larger amount of root exudates entering the soil (Cuong et al 2023). Plant biomass parameters (involving understory plant biomass and litter biomass) are positively correlated with soil nutrient concentrations (Table 1), illustrating the accumulation of soil nutrient contents with increasing plant biomass, which is due to the important regulation of plant biomass on soil nutrient concentrations.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results agree with those from earlier studies (Zhao et al 2014;Liu et al 2016;Cuong et al 2023). These findings may be explained by a significantly greater plant litterfall production and fine-root turnover in older plantations and a larger amount of root exudates entering the soil (Cuong et al 2023). Plant biomass parameters (involving understory plant biomass and litter biomass) are positively correlated with soil nutrient concentrations (Table 1), illustrating the accumulation of soil nutrient contents with increasing plant biomass, which is due to the important regulation of plant biomass on soil nutrient concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…The findings from this study indicated that soil nutrient concentrations (SC, SN, and SP) increased significantly with increasing age in Acacia hybrid plantation. These results agree with those from earlier studies (Zhao et al 2014;Liu et al 2016;Cuong et al 2023). These findings may be explained by a significantly greater plant litterfall production and fine-root turnover in older plantations and a larger amount of root exudates entering the soil (Cuong et al 2023).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations